2016
DOI: 10.1136/thoraxjnl-2015-207696
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of small pulmonary vessels area in patients with COPD with severe pulmonary hypertension

Abstract: CT measurements of small vessels support a distinct vessel-related phenotype in patients with COPD with severe PH, and combined with WT and PaO2 parameters in the paw score, which may offer a non-invasive tool to select patients for RHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 37 publications
7
55
0
Order By: Relevance
“…CT studies showed that emphysema extent was correlated to blood vessel pruning (CSA <5 mm 2 ), thereby highlighting a pulmonary vascular phenotype [22,135,136]. This decreased proportion of small pulmonary vessels has also been linked with pulmonary hypertension [116] and clinical outcomes [137] in COPD patients.…”
Section: Pulmonary Vascularisationmentioning
confidence: 98%
“…CT studies showed that emphysema extent was correlated to blood vessel pruning (CSA <5 mm 2 ), thereby highlighting a pulmonary vascular phenotype [22,135,136]. This decreased proportion of small pulmonary vessels has also been linked with pulmonary hypertension [116] and clinical outcomes [137] in COPD patients.…”
Section: Pulmonary Vascularisationmentioning
confidence: 98%
“…The small pulmonary vessels measurements were made automatically as described elsewhere (4, 10-12). The cross section area (CSA) and cross section number (CSN) of small pulmonary vessels were quantified separately at the subsegmental and at the sub-subsegmental levels (4,12). The subsegmental and sub-subsegmental levels are defined by a vessel area between 5 and 10 mm 2 and less than 5 mm 2 , respectively.…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…Our hypothesis is also supported by Coste et al. [21], who recently observed using CT a specific increase in total cross-sectional area and an increase in the number of small vessels (<5 mm 2 ) in COPD patients with severe PH compared to COPD patients without severe PH.…”
Section: Discussionmentioning
confidence: 98%